Tuberculosis-associated anemia is linked to a distinct inflammatory profile that persists after initiation of antitubercular therapy - Gil-Santana, Leonardo; Cruz, Luís A. B.; Arriaga, María B.; Miranda, Pryscila F. C.; Fukutani, Kiyoshi F.; Silveira-Mattos, Paulo S.; Silva, Elisangela C.; Oliveira, Marina G.; Mesquita, Eliene D. D.; Rauwerdink, Anneloek; Cobelens, Frank; Oliveira, Martha M.; et al. (Scientific reports, 2019)
Pulmonary tuberculosis (PTB) is associated with chronic inflammation and anemia. How anemia impacts systemic inflammation in PTB patients undergoing antitubercular therapy (ATT) is not fully understood. In the present study, data on several blood biochemical parameters were retrospectively analyzed from 118 PTB patients during the first 60 days of ATT. Multidimensional statistical analyses were employed to perform detailed inflammatory profiling of patients stratified by anemia status prior to treatment. Anemia was defined as hemoglobin levels <12.5 g/dL for female and <13.5 g/dL for male individuals. The findings revealed that most of anemia cases were likely caused by chronic inflammation. A distinct biosignature related to anemia was detected, defined by increased values of uric acid, C-reactive protein, and erythrocyte sedimentation rate. Importantly, anemic patients sustained increased levels of several biochemical markers at day 60 of therapy. Preliminary analysis failed to demonstrate association between persistent inflammation during ATT with frequency of positive sputum cultures at day 60. Thus, TB patients with anemia exhibit a distinct inflammatory profile, which is only partially reverted at day 60 of ATT.